2013
DOI: 10.5267/j.msl.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of intellectual capital components on each others and organizational learning capabilities

Abstract: During the past few years, there have been growing interests on intellectual capital due to industrial changes on the market. Thus, identifying different ways to create, manage, and evaluate the impact of intellectual capital has remained an open area of research. One of the most important organizational capabilities, which could help organizations create and share knowledge is to effectively use knowledge to create competitive advantage. The primary objective of this study is to investigate the effects of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Saadi and Pahlavani (2012) confirmed that all three IC items positively influence knowledge creation, significantly. Darvisha et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saadi and Pahlavani (2012) confirmed that all three IC items positively influence knowledge creation, significantly. Darvisha et. al.…”
Section: Literature Reviewmentioning
confidence: 99%